Evaluation of color, water content, and antioxidant properties of wood ear mushroom with nano edible coating, packaging, and storage temperature - Rachman, Aulia Afifah; Hamdani, Jajang Sauman; Kusumiyati, Kusumiyati (Kultivasi, 2025)
Wood ear mushrooms are often consumed in Asia and Tropical America for their jelly-like texture, health, and freshness. However, they are easily damaged due to microbes and poor postharvest handling, which affects quality. The combination of nano edible coating, packaging, and storage temperature offers a solution to these issues. This study aims to evaluate the effect of nano edible coating, packaging, and storage temperature on the color (L*, a*, and b*), water content, and antioxidant properties (total phenolic and flavonoid) of wood ear mushrooms. The study was conducted at the Horticulture Laboratory, Faculty of Agriculture, Universitas Padjadjaran. The experimental design used was a Completely Randomized Design with a total of 18 combinations of nano edible coating (sodium alginate and aloe vera), packaging (biodegradable, wrap, and vacuum plastic), and storage temperature (±25 ℃, 10 ℃, and 5 ℃). Each treatment was replicated twice, resulting in 36 experimental units, with 3 mushrooms per unit for a total of 108 mushrooms. The results showed a significant effect of the combination treatments on L* at 9 days after treatment (DAT), a* at 6 DAT, water content at 6 and 9 DAT, total phenolics, and total flavonoids during the storage period. Nano aloe vera with vacuum packaging at 5 ℃ gave the best effect on L* value at 9 DAT, water content at 6 and 9 DAT, total phenolic at 3 and 6 DAT, and total flavonoid at 6 DAT. These results indicated the potential of the treatment in maintaining the quality of the wood ear mushroom during storage.